BUILDING A TRUSTED AND RISK-RESILIENT DIGITAL FINANCIAL ECOSYSTEM: A GOVERNANCE FRAMEWORK FOR MSME SCALING IN INDONESIA - Wiwiek Prihandini; Andi Fariana; Siti Safaria; Andyni Yulfanis Aulia Masrifa (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
Digital transformation has created new opportunities for micro, small, and medium enterprises (MSMEs) to expand access to finance, reach wider markets, and improve business efficiency through digital financial services. At the same time, the rapid adoption of digital technologies has introduced new challenges, including digital fraud, cyber threats, data misuse, platform dependency, and emerging risks associated with artificial intelligence. These developments suggest that the success of MSME digitalization depends not only on technological advancement and financial access but also on the level of trust and resilience within the digital financial ecosystem. This study develops a governance framework to support the creation of a trusted and risk-resilient digital financial ecosystem that enables sustainable MSME scaling in Indonesia. The study adopts a qualitative conceptual approach based on a comprehensive literature review, thematic analysis, and the synthesis of academic studies, policy documents, and institutional reports. The findings indicate that trust and risk resilience play a pivotal role in linking the digital financial ecosystem to MSME growth and long-term sustainability. Building on these findings, the study proposes the Trusted and Risk-Resilient Digital Financial Ecosystem Governance Framework (TRR-DFEG Framework), which comprises five interrelated pillars: digital trust governance; cyber and operational resilience governance; data governance and responsible AI; consumer protection and capability governance; and collaborative ecosystem governance. The framework offers a conceptual foundation and practical policy guidance for regulators, financial institutions, and other stakeholders seeking to build a secure, inclusive, and sustainable digital financial ecosystem that supports MSME development. Keywords: digital financial ecosystem; governance; trust; risk resilience; MSMEs; financial system stability.